Pengaruh Terpaan Iklan dan Kredibilitas Celebrity Endorser Biore UV X Stray Kids di Tiktok terhadap Keputusan Pembelian di Kota Semarang - Dwi Indrawati; Mubarok Mubarok (INDO PUBLISHING, 2026)
The development of social media, particularly TikTok, has transformed marketing communication strategies, including the use of celebrity endorsers to promote beauty products. One example is the Biore UV x Stray Kids advertising campaign, which targets young consumers. This study aims to examine the effect of advertising exposure and celebrity endorser credibility of Biore UV x Stray Kids on TikTok on consumers’ purchasing decisions in Semarang City. This study employed a quantitative approach involving 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that advertising exposure has a positive and significant effect on purchasing decisions (t = 12.502; sig. = 0.000), while celebrity endorser credibility also has a positive and significant effect (t = 6.227; sig. = 0.000). Simultaneously, both variables have a significant effect on purchasing decisions (F = 111.154; sig. = 0.000), with an R² value of 0.696. This indicates that advertising exposure and celebrity endorser credibility explain 69.6% of the variation in purchasing decisions, while the remaining 30.4% is explained by other factors. Advertising exposure has a greater influence than celebrity endorser credibility. This study uses the Stimulus–Organism–Response (S-O-R) theory as the grand theory to explain that advertising exposure and celebrity endorser credibility as stimuli can generate a consumer response in the form of purchasing decisions.